Analysis of Strong Wind Characteristics Using Doppler Weather Radar over Kualanamu Airport Indonesia - Manurung, Ellya Veronika Iriani; Humaidi, Syahrul; Darmawan, Yahya (Journal of Applied Geospatial Information, 2024)
Strong wind is one of the weather phenomena that can be dangerous for aviation safety. According to observation data from the Kualanamu Meteorological Station, there were 61 strong winds with speeds greater than or equal to 15 knots in 2020, which indicates a high risk of strong wind over this area. This research aims to analyze the characteristics of strong winds in the Kualanamu airport area using weather Doppler radar. The data used consisted of nine cases of the strongest winds for each month in 2020. We have tested analysis methods of radar products such as VVP, CAPPI V, and PPI on nine sample dates to determine the duration, intensity, and direction of wind speed. Additionally, we used the radar's echo pattern to identify the potential impact of cumulonimbus clouds (Cb), which trigger strong winds. Three out of nine study cases, identified as the three most significant strong winds during 2020, have been subjected to echo pattern analysis. The results showed that the strong winds occur for 40 to 70 minutes, but they mostly have a duration of about 50 minutes. Overall, strong winds occurred during the night and early morning. The radar echo typically has a range between 18 and 43 dBZ. Echo patterns generally revealed a group that extended in the shape of a squall line that moved from west to east and reversed.